Permeability Characteristics of Combined Coal with Different Water Contents - Hongyu Pan; Yao Zhang; Lei Zhang; Yan Cao; Yuhang Chu; Shihua Yang (Energies)
Hydraulic fracturing changes the stress state of the coal body, and the residual water within the coal body after fracturing affects its permeability characteristics. To examine the impact of hydraulic measures on the permeability of coal under varying water contents and radial stress distributions, permeability tests were conducted using the improved LFTD1812 triaxial permeameter. The flow rate of coal under different water content combinations was measured, and the permeability, pressure gradient, and seepage velocity of the samples were calculated. The relationships among porosity, permeability, pressure gradient, and seepage velocity were analyzed. The effect of water content on permeability was evaluated, and the directional behavior of permeability was identified. The results showed that the porosity of the samples with water contents of 25%, 17.5%, and 10% decreased by 48.5%, 23.9%, and 17.6%, respectively, during the loading process. The permeability of all samples ranged from 1.91 × 10−13 m2 to 76.91 × 10−13 m2. As the absolute value of the pressure gradient increased, the downward trend of permeability was categorized into three stages: rapid, slow, and stable. Higher water content corresponded to lower initial permeability, with the permeability–pressure gradient curve shifting downward. Additionally, the slow decline zone moved to the right, and the absolute value of the pressure gradient required to enter this zone decreased. Seepage velocity consistently decreased with increasing water content across all osmotic pressure levels, although the rate of decline progressively weakened. The maximum permeability difference between the forward and reverse samples was 10.48 × 10−13 m2. Permeability directionality decreased with increasing equivalent water content and osmotic pressure, with water content identified as the primary influencing factor. Permeability variations caused by axial compression were divided into three phases: the weak influence of the polarization effect, the transition phase, and the strong influence phase. These findings confirm that water content has the most significant impact on permeability, demonstrating that gas flow primarily follows the principle of distance priority toward the nearest borehole. Boreholes closer to the source exhibit higher extraction volumes. These results provide theoretical support for improving coal permeability, enhancing gas drainage efficiency, and preventing gas accidents through hydraulic measures.